Художественный аспект в мемуарах Дж. Сейдамета «Базы хатыралар» («Некоторые воспоминания») - Куршутов, Т.Н. (Культура народов Причерноморья, 2013)
В статье рассматриваются художественные особенности воспоминаний Джафера
Сейдамета «Базы хатыралар», являющиеся одним из ярких произведений мемуарного жанра
крымскотатарской литературы первой половины XX века. Хронологически мемуары охватывают
период между русской революцией 1905 года и установлением советской власти в Крыму в 1920 году,
являющийся одним из драматических и кровавых эпизодов в истории крымскотатарского народа. У статті розглядаються художні особливості спогадів Джафера Сейдамета «Деякі
спогади», що є одним з яскравих творів мемуарного жанру кримськотатарської літератури першої
половини XX століття. Хронологічно мемуари охоплюють період між російською революцією 1905 року
і встановленням радянської влади в Криму в 1920 році, що є одним з драматичних і кривавих епізодів в
історії кримськотатарського народу. The artistic features of J. Seydamet memoirs «Some memoirs» which was one of the best works of
the memoir genre in Crimean Tatar literature of the first half of the XX century discusses in the article. The
memoirs covers the period between the Russian Revolution (1905) and the establishment the Soviet authority in
Crimea in 1920, which was one of the most tragic periods in the history of Crimean Tatars.
The various aspects of the artistic features of the work analyse in the article. Such pecularities as poetic
originality, style of representation, the language of the narrative, unusual representation the portraits of
contemporaries, including well-known public and political persons of the Crimea, Ukraine, Russia, Poland,
Turkey, Germany such as M. Hrushevsky V. Vynnychenko, S. Petliura, A. Kerensky, J. Pilsudsky, Talyat and
Enver Pasha shows at this point.
The article opens the sence and value «Some memoirs» as the most important source of information the history
of the Crimea of the first two decades of the XX century, and especially the events of 1917-1918, which has the
marginal meaning in the national revival of the Crimean Tatar people. The memories combined the truth of the
historical document and work of art of high artistic beauty.